STRATEGI PERENCANAAN AGREGAT SEBAGAI PILIHAN KAPASITAS PRODUKSI - Harry Indra (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
The purpose of this research is to provide solutions that can be given to firm to face the problems and to provide recommendations that can be given to the company to fulfill the order request number in a timely manner and achieve a level of production that the company expected. In this research, these problems can be resolved with 2 steps. First, forecasting consumer demand in the future with 4 methods, Linear Regression, Moving Average, Weighted Moving Average and Exponential Smoothing based on previous demand data and Second, using aggregate planning methods with 3 alternative strategies, there are Chase Strategy, Level Strategy and Mixed Strategy. Advice can be given to company is where firm can implement Mixed strategy, because this strategy has the most minimal total cost of production compared to 2 others strategies